PERAN KEPALA SEKOLAH DALAM MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) - Mahfudhoh, Noviana Ulfah; Rasidi, Rasidi (Universitas Muhammadiyah Magelang, 2015)
This study aimed to describe the condition of school-based management quality improvement, supporting factors and inhibitingfactors management school based quality improvement, as well as the principal’s role in the management of school based qualityimprovement.This research uses descriptive quantitative method. Subjects in this study were principals and objects in this study isbased on improving the quality of school. Source of research data is the principal, teachers, and the school community. Dataobtained through questionnaires, interviews, and observations.The result showed that the role of the principal in the management of school based quality improvement at theelementary sekecamatan Ngadirejo Temang- has run quite effectively. Pendukunnya factor is teacher resources which areadequate, facilities and infrastructure are adequate, innovation that has made the principal. Inhibiting factor is the lack of booksowned by the school, a library room that has not been used optimally. Based on observations, interviews and questionnaires werecarried out, the value of an average of 84%. These results illustrate that the principal’s role in the management of school basedquality improvement and the principal result was very instrumental in the management of school based quality improvement.